2003
DOI: 10.1007/s00428-002-0748-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathology of non-invasive urothelial carcinomas (part I)

Abstract: An international consultation on the diagnosis of non-invasive urothelial neoplasms was held in Ancona, Italy in May 2001. Besides histology and problems of classification, one group of experts (Committee no. 3) discussed the molecular pathology and cytometry of noninvasive urothelial carcinomas. In the following first part, special immunohistochemical and molecular markers for stratifications in bladder cancer were discussed including different cytokeratins (clone 34bE12, CK 20), cell proliferation markers (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 48 publications
1
14
0
2
Order By: Relevance
“…An important goal of array investigations of UC is the development of biomarkers for prognostic purposes. This aim has so also been pursued by investigations focused on individual genes, the most prominent one being TP53 32, 33, 34. The TP53 tumor suppressor gene harbors missense mutations in up to 50% of bladder cancers.…”
Section: Tp53 As a Biomarker In Ucmentioning
confidence: 99%
See 2 more Smart Citations
“…An important goal of array investigations of UC is the development of biomarkers for prognostic purposes. This aim has so also been pursued by investigations focused on individual genes, the most prominent one being TP53 32, 33, 34. The TP53 tumor suppressor gene harbors missense mutations in up to 50% of bladder cancers.…”
Section: Tp53 As a Biomarker In Ucmentioning
confidence: 99%
“…Moreover, LOH at 17p is preferentially found in advanced cases. Evidently, TP53 mutations are associated with an increased risk of progression in bladder cancer 3, 4, 32, 33, 34. The moot point is whether detection of TP53 mutations can predict the natural course of the disease or responses to therapy better than histopathological parameters.…”
Section: Tp53 As a Biomarker In Ucmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 On the other hand, papillary bladder cancer comprises different types of tumors with varying biologic potential and distinct pathways of development. 5,6 The 5-year survival rate is approximately 94% in patients with localized bladder cancer but decreases to 6% in those developing metastatic disease. 7 Early detection of primary and recurrent, potentially aggressive bladder cancer is thus an important determinant of treatment success.…”
mentioning
confidence: 99%
“…In the present study 84 % cases could achieve a histological diagnosis on basis of histomorphology alone, and in 16 % cases IHC was required for final diagnosis, mainly to differentiate between Papillomas / Non-invasive PUNLMP/Non-invasive PUCLG. Many studies done by Alrashidy et al [15] Eble et al [8] Mallofre et al [13] Helpap et al [16] have also reported that distinguishing urothelial papillomas/ PUNLMP and papillary carcinomas especially non-invasive low grade one is sometimes difficult on the basis of histomorphological features alone and IHC markers may be used as an adjuvant to histology to arrive at a final diagnosis in these cases. IHC markers (CK20, p53 and Ki67) were applied on cases with differential diagnosis of UP / PUNLMP, IP/ PUCLG, UP/ PUCLG and PUNLMP/ PUCLG.…”
Section: Discussionmentioning
confidence: 99%